Imaging Review of Skeletal Tumors of the Pelvis—Part I: Benign Tumors of the Pelvis - Girish, Gandikota (The Scientific World Journal, 2012)
The osseous pelvis is a well-recognized site of origin of numerous primary and secondary musculoskeletal tumors. The radiologic evaluation of a pelvic lesion often begins with the plain film and proceeds to computed tomography (CT), or magnetic resonance imaging (MRI) and possibly biopsy. Each of these modalities, with inherent advantages and disadvantages, has a role in the workup of pelvic osseous masses. Clinical history and imaging characteristics can significantly narrow the broad differential diagnosis for osseous pelvic lesions. The purpose of this review is to familiarize the radiologist with the presentation and appearance of some of the common benign neoplasms of the osseous pelvis and share our experience and approach in diagnosing these lesions.